Effect of alfalfa hay quality in an alfalfa–maize diet on the digestion, metabolism, and growth rate of goats in the Longdong Loess Plateau - Yuhong Jiang; Jieyan Zhou; Xianjiang Chen; Ying Kang; Tianhai Yan; Fujiang Hou (Grassland Research)
Abstract Background To optimize animal production systems for future sustainability, research now focuses on improving feed quality to enhance livestock performance. Here, we test the impact on goat metabolism of varying leaf proportions in the alfalfa component of an alfalfa–maize diet. Methods In a pen‐feeding experiment, 16 three‐month‐old goats were divided into eight groups, four of which were fed a ration containing 40% alfalfa with leaves intact (LI) and four of which were fed an otherwise identical diet containing stemmy alfalfa (leaves removed, LR). Results As expected, LR reduced protein intake compared to LI (48.3 vs. 93.3 g d−1; p < 0.001) and increased acid detergent fiber intake (239 vs. 167 g d−1; p < 0.001), but neutral detergent fiber and dry matter digestibility did not differ between LR and LI. The LR group had lower gross energy, digestible energy, and metabolizable energy intakes than the LI group (p = 0.080, 0.030, and 0.022, respectively). Retained nitrogen for LI and LR was 2.30 and 1.72 g d−1, respectively. Body weight gain was 74 g d−1 in LI and 52 g d−1 in LR (p < 0.001). Conclusions These results highlight that even where alfalfa is only one component of a mixed diet, the nutritive quality and leaf content of the alfalfa component are important to animal performance.